A experiência de moradia do idoso: suas relações com o processo de escolha e o bem-estar subjetivo - Bins, Leticia Nobre (2020)
Studies on the relationships between the environment and the wellbeing of the elderly have been widely explored in the field of gerontology and health in general. However, since housing is a type of consumption choice, when analyzing it from such perspective studies are scarce; so it is necessary to deepen the understanding of the experience of housing in the elderly. Thus, this dissertation aims to identify the relationships between the process of choosing the residence, the dimensions of the elderly consumer’s living experience and their subjective well-being. In order to achieve this purpose, this exploratory qualitative study conducted in-depth interviews with the elderly in two housing models: their own (apartment) and residential home for the elderly. Seventeen elderly people aged between 66 and 100 years were interviewed, representatives of the two housing models and a manager of the elderly home. The analysis of the data from the interviews made it possible at first to depict an integral view of the dimensions of the housing experience in two different models: own residence and elderly residential, where the dimensions of Residence Design and Emphasis on Social Aspects are the most valued, respectively, in both models. However, they showed differences in the importance of the other dimensions and aspects for the elderly when analyzing them individually in each model and between models. The analysis also allowed to detect the existence of different motivations in the search for housing as well as which aspects of the housing experience were considered for each of the motivations. It was possible to identify that the choice of housing is not always a decision of the elderly person but sometimes a family choice. Another result of the analysis was the understanding of which aspects influence the subjective well-being of the elderly in the different housing models, which made it possible to conclude that the elderly are making good choices. Thus, the analyses made it clear that the dimensions of the housing experience most valued in the choice of residence models coincide with the dimensions that most influenced the subjective well-being of the elderly.